On studies of Lithuanian folk pedagogy - Lazauskienė , M. (Psichologija, 1971)
The paper deals with the necessity of investigating Lithuanian folk pedagogy and makes reference to some investigations carried on in the Soviet Union and the countries of People’s Democracies. Methodological basis is followed by an analysis of the main sources used for investigation of Lithuanian folk pedagogy which brings forth a number of problems pertaining to the history of pedagogics. The paper discusses certain aids of folk pedagogy collected from elderly people during an expedition to Kernavė in 1969.